Whole-genome resequencing and transcriptional profiling association analysis revealed the intraspecies difference response to oligosaccharides utilization in Bifidobacterium animalis subsp. lactis - Lan, Zhenghui; Zhang, Xueling; Xu, Meng; Kong, Junkai; Zuo, Xuancheng; Wang, Yixuan; Wang, Chenxi; Teng, Yingdi; Ni, Yongqing; Zhang, Yan (Frontiers in Microbiology, 2024)
As prebiotics, oligosaccharides are frequently combined with Bifidobacterium to develop synbiotic products. However, a highly diverse gene repertoire of Bifidobacterium is involved in sugar catabolism, and even phylogenetically close species may differ in their sugar utilization capabilities. To further explore the mechanism underlying the differences in Bifidobacterium animalis subsp. lactis oligosaccharide metabolism, this study screened strains with differential oligosaccharide metabolism. Subsequently, these strains were subjected to genome-wide resequencing and RT-qPCR. The resequencing results indicated that the subspecies of B. animalis subsp. lactis had a high genome similarity. The RT-qPCR results revealed that glycosidase genes exhibited consistency in the phenotype of metabolism at the transcriptional level; the better the growth of the strains on the oligosaccharides, the higher was the expression of glycosidase genes related to the oligosaccharides. Our results suggested that the differences in the gene transcription levels led to intraspecies differences in the ability of the strains to metabolize oligosaccharides even when they belonged to the same subspecies. Future studies with more sample size could generalizable the conclusion to all B. animalis subsp. lactis strains, thus would lay the theoretical foundation for the utilization of the B. animalis subsp. lactis strain as probiotics and the development of synbiotic products.